The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.4081/hr.2012.e15
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell Acute Lymphoblastic Leukemia with t(4;11)(q21;q23) in a Young Woman: Evolution into Mixed Phenotype Acute Leukemia with Additional Chromosomal Aberrations in the Course of Therapy

Abstract: About 5% of adult B-cell acute lymphoblastic leukemias (B-ALL) are characterized by t(4;11)(q21;q23), which confers peculiar features to this B-ALL subtype, including a very immature immunophenotype and poor prognosis. We describe the case of a 21-year-old female who presented with B-ALL carrying the t(4;11)(q21;q23) and blasts positive for CD19, TdT, CD79a, CD38, HLA-DR. Before completing the Hyper-CVAD (hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone) therapy regimen, the B-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Patients with t(4;11) MLL-AF4 leukemia present with an expansion of leukemic blasts that have a phenotype similar to pro-B cells (CD19 1 CD10 2 ) and retain myeloid features (CD15 1 ), and myeloid leukemic clones can emerge during disease progression. 50,51 This suggests that the cell-of-origin of t(4;11) MLL-AF4 B-ALL retains lymphoid and myeloid potential, which could explain the lineage switch observed in some patients following treatment. [52][53][54] In Mll-AF4 1 miR-130b 1 mice, we also observed a coexpression of myeloid and lymphoid markers on a substantial proportion of leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with t(4;11) MLL-AF4 leukemia present with an expansion of leukemic blasts that have a phenotype similar to pro-B cells (CD19 1 CD10 2 ) and retain myeloid features (CD15 1 ), and myeloid leukemic clones can emerge during disease progression. 50,51 This suggests that the cell-of-origin of t(4;11) MLL-AF4 B-ALL retains lymphoid and myeloid potential, which could explain the lineage switch observed in some patients following treatment. [52][53][54] In Mll-AF4 1 miR-130b 1 mice, we also observed a coexpression of myeloid and lymphoid markers on a substantial proportion of leukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The other three cases demonstrated an immunophenotype switch, previously reported in MLL rearranged leukemias. [22][23][24][25][26][27] MLL rearrangement juxtaposes the amino-terminus of the histone methyltransferase MLL with a variety of different fusion partners. To date, more than 70 fusion partners of the MLL gene have been characterized.…”
Section: Mll Rearrangement and Immunophenotype Switchmentioning
confidence: 99%
“…B-ALL evolving into MPAL has only once been described in the literature before. Carulli et al reported a case of a 21-year-old female with B-ALL associated with t(4;11)(q21;q23) who was treated with the Hyper-CVAD regimen, and during the course of therapy (after 6 of 8 planned cycles) had evolved into MPAL with additional chromosomal aberrations [16]. In regards to the incidence of lineage switch from B-ALL to frank AML at relapse, only sparse reports exist, most of which are associated with KMT2A-rearranged infant B-ALL [17][18][19][20][21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%